2009
DOI: 10.1007/s12565-009-0069-3
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial bridges of the coronary arteries in the human fetal heart

Abstract: During the last century, many investigators reported on myocardial bridges in the adult human heart. In the present study, 39 human fetal hearts (the mean gestastional age was 30 weeks) were studied for myocardial bridging, and the results were correlated with adult data. Among the 39 (27 male and 12 female) fetal hearts studied, 26 bridges were observed on 18 fetal hearts (46.2%). Ten of the bridges had one myocardial bridge, whereas double myocardial bridges were observed in eight fetal hearts. The most freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
0
13
1
4
Order By: Relevance
“…Cardiac arrhythmia and coronary artery spasm are triggered by autonomic nerve fibers innervating the myocardial bridges (Cao et al, ; Yasue et al, ), so the autonomic innervation of the heart near myocardial bridges is important. Myocardial bridges are also observed in human fetal hearts (Cakmak et al, ), suggesting that they form temporarily during the fetal period. Tian et al () revealed that coronary arteries and cardiac veins are formed from common precursor cells in the mouse, so it is also important to examine the course and distribution pattern of cardiac veins at the myocardial bridges.…”
Section: Introductionmentioning
confidence: 92%
“…Cardiac arrhythmia and coronary artery spasm are triggered by autonomic nerve fibers innervating the myocardial bridges (Cao et al, ; Yasue et al, ), so the autonomic innervation of the heart near myocardial bridges is important. Myocardial bridges are also observed in human fetal hearts (Cakmak et al, ), suggesting that they form temporarily during the fetal period. Tian et al () revealed that coronary arteries and cardiac veins are formed from common precursor cells in the mouse, so it is also important to examine the course and distribution pattern of cardiac veins at the myocardial bridges.…”
Section: Introductionmentioning
confidence: 92%
“…In forensic autopsies, it is sometimes considered a cause of sudden death and is often reported as such in scientific articles, especially in association with other congenital cardiac or coronary anomalies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). It is considered an inborn anomaly, being found in studies on human fetuses (21), and it appears to reflect particular developmental processes within the heart (22). The description of the morphological characteristics of MBs is extremely heterogeneous in the scientific literature.…”
mentioning
confidence: 99%
“…The higher frequency of MB detection at autopsy than with MDCT may be due to differences between these methods, because an MB thinner than 200 μm can only be detected by autopsy. Furthermore, MBs have already been recognized in the LAD of a neonate, 42 an infant suffering a myocardial infarction (MI), 43 and autopsied fetal hearts, 41 indicating that the MB is a chance congenital anatomical structure.…”
mentioning
confidence: 99%